PANEL REGRESSION INVESTIGATION ON THE IMPACT OF SERVICE EXPORT AND AGRICULTURAL RAW MATERIALS ON ECONOMIC GROWTH IN 5 SUB-SAHARAN COUNTRIES - Akobundu, Nkem Juliet; Adenomon, M. O.; Maijama’a, Bilkisu (FUDMA JOURNAL OF SCIENCES, 2024)
Population expansion, rising incomes, and increasing urbanization characterize Sub-Saharan Africa's economies, indicating potential market development but also posing trade stability problems. Poor economic performance and dependency on oil exports in the region have necessitated additional research and talks. This study will look into the impact of service exports and agricultural raw materials on the economic growth of five Sub-Saharan African countries between 2012 and 2022. The study will examine the impact of service exports (sexp) and agricultural raw materials (aexp) on GDP using several regression models, to determine the most appropriate model using the Hausman test. The research seeks to establish the relationship between service exports, agricultural raw material exports, and economic growth in these countries, chosen based on their GDP performance as of 2023. The study used three different estimators to ensure robust results. The Hausman test revealed that the fixed effects model is most suitable for addressing challenges related to independent variables with a positive but negligible impact on GDP. Overall, the research found that while service exports have a positive impact, it is statistically insignificant for GDP. The findings are also applicable to agricultural raw materials. The consistent and large value shows that an increase in service exports and agricultural raw materials will increase the selected Sub-Saharan African countries' GDP. According to the findings, authorities in these countries should develop policies to establish conditions that promote the productive and advantageous roles of agricultural raw materials and service exports in driving economic expansion across Sub-Saharan Africa.